(untitled) - Bala, Raghuram (Indianapolis, IN, 1996)
Que's Special Edition Using Optima++ 1.5 is the comprehensive reference for serious programmers. With practical, real-world examples that illustrate difficult concepts and complete coverage of the topics you need to know, this is the all-in-one, complete Optima++ learning kit. Not only will you gain expert tutorial and reference advice, but by using the software included in this book, you'll also learn the language and get helpful tips and techniques.
Keywords: C (Ngôn ngữ chương trình máy tính),C (Computer program language)